Makna Budaya dalam Slogan Demonstrasi Mahasiswa: Kajian Antropolinguistik - Arfa Aulia Parinduri; Florentina Verena; Nadya Putri Ramadhani; Yupita Aswaliyah; Ida Basaria (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2026)
This study examines the cultural meanings contained in student protest slogans during the October 2025 demonstrations using an anthropolinguistic approach. Language in protest slogans functions not only as a communication tool but also as a cultural representation reflecting social values, ideology, collective identity, and social practices. The purpose of this study is to reveal the cultural meanings embedded in student protest slogans and explain how these meanings are constructed through linguistic choices. This research employs a descriptive qualitative method with observation, note-taking, documentation, and brief interviews with participants as data collection techniques. The data were analyzed using distributional methods by identifying linguistic elements such as metaphors, irony, lexical choices, and sentence structures, then relating them to socio-cultural contexts. The findings show that protest slogans represent values of social solidarity, nationalism, social justice, transparency, criticism of power, gender equality, and resistance to state repression. In addition, slogans construct collective identities between citizens, government, and authorities, while carrying strong socio-political ideologies. These findings confirm that protest slogans are complex cultural practices and reflect students’ collective awareness in responding to social dynamics.